Estimation of the performance of a BIPV façade in working conditions through real monitoring and simulation. (August 2018) - Bellazzi, Alice; Belussi, Lorenzo; Meroni, Italo
Abstract: A module of ceramic tile with integrated a silicon amorphous thin film solar cell was tested in working conditions. The ceramic modules were installed on a ventilated façade in a 3 stories laboratory building completely equipped with sensors to detect the thermal and energetic behavior of the prototype. The experimental campaign aimed at monitoring the energy and thermal performances of the ventilated BIPV façade in the current configuration. The paper describes the output of the experimentation. Specifically, the operative temperature, the global efficiency and the electric production of the system have been evaluated in real working condition.